Models of Intermediate Care Organization and Staffing at an Academic Medical Center: Considerations of an Inpatient Planning Committee. (October 2022) - Hager, David N.; Dezube, Rebecca; Disney, Sarah M.; Flanagan, Eleni; Huang, Shanshan; Kakadiya, Kinjal; Langlotz, Ronald; Lautzenheiser, Matthew B; Street, Lara; Michalek, Andrew; Biddison, Lee D.; Desai, Sanjay V.; et al.
Rationale: Geographic co-localization of patients and provider teams (geography) may improve care efficiency and quality. Patients requiring intermediate care present a unique challenge to the geographic model.Objective: Identify the best organizational and staffing model for intermediate care at our academic medical center.Methods: A modified nominal group technique was employed to assess the benefits and limitations of an existing model of intermediate care, identify and review potential alternative models, and choose a new model.Results: In addition to the institution's current model, the benefits and limitations of six alternative organizational and staffing models were characterized. The anticipated impact of each model on nurse: provider communication, maintenance of nursing competencies, nurse satisfaction, efficient utilization of technical and human resources, triage of patients to the unit, care continuity, and the impact on trainee education are described. After considering these features, stakeholders ranked a closed provider staffing model on a unit dedicated to intermediate care highest of the six alternative models. Important outcomes to monitor following transition to a closed staffing model included patient outcomes, nursing job satisfaction and retention, provider and trainee experience, unexpected patient transfers to higher or lower levels of care, and administrative costs.Conclusions: After considering six alternative staffing models for intermediate care, stakeholders ranked a closed provider staffing model highest. Further qualitative and quantitative comparisons to determine optimal models of intermediate care are needed.